Effect of an innovative mattress and cryotherapy on sleep after an elite rugby match - Aloulou, A.; Leduc, C.; Duforez, F.; Piscione, J.; Cheradame, J.; Bieuzen, F.; Thomas, C.; Chennaoui, M.; van Beers, P.; Nedelec, M. (Medicine & Science in Sports & Exercise, 2020)
Introduction: This study aimed to explore the relationship between elite rugby union match and postmatch sleep architecture and to investigate the effects of a high-heat capacity mattress (MAT) and a whole-body cryotherapy (WBC) session on postmatch sleep architecture.